Urgensi Pembelajaran Bahasa Arab dalam Pendidikan Islam - Asna Andriani (Institut Agama Islam Negeri (IAIN) Tulungagung, 2015)
Language is very important for everyone used to deliver information, ideas, and thought from a person to others. One of the oldest languages in this world is Arabic. It is used in oral and written form and it contributes to the development of Islamic thought tradition in some Islamic texts such as Qur’an, Hadits, Tafsir, Fiqih, Tasawuf, etc. Therefore, it is very important for Moslems to learn Arabic language especially in the realm of Islamic education as to gain deep understanding about the substances or contents (meaning sense) of the text. This article discusses about the important roles of Arabic in islamic education to increase the faith quality and good behavior of Moslems.